Land-use impacts on benthic macroinvertebrate assemblages in pampean streams (Argentina). (1st February 2021) - Marrochi, María Natalia; Hunt, Lisa; Solis, Marina; Scalise, Ana María; Fanelli, Silvia Laura; Bonetto, Carlos; Mugni, Hernán
Abstract: In recent decades agriculture has intensified in the Argentine Pampa, and pesticide application has also increased. Livestock fields, although being progressively replaced by crops, are still commonly interspersed with crop fields. The objective of the present work is to assess the effects of land use on the benthic invertebrate assemblages of streams in the main Argentine agricultural region. Two areas were sampled during the 2011/12 growing season (November–March): Arrecifes, a homogeneous intensively cultivated area, and La Plata, a heterogeneous area of mixed livestock pasture, cropland and biological reserve. Nutrient concentrations in water were significantly higher in the streams surrounded by cropland. Measured pesticides in stream sediments were those most commonly used in crop production: chlorpyrifos, cypermethrin, lambda-cyhalothrin, endosulfan and its degradation product endosulfan sulfate. Detection frequency and pesticide concentrations were generally higher in streams surrounded by cropland than in streams surrounded by pasture or reserve. Macroinvertebrate assemblages were significantly different in streams with different land uses. Palaemonidae (Decapoda) and Caenidae (Ephemeroptera) were the taxa best represented in the reserve. Hyalellidae (Amphipoda) and Hirudinea were dominant at the streams surrounded by livestock fields. Within the streams surrounded by croplands, Oligochaeta and Hirudinea were best represented in La Plata while Chironomidae, Gastropoda and Oligochaeta were dominant at Arrecifes. Present evidence suggests that agrochemical applications contribute, in combination with other environmental variables, to the observed differences in macroinvertebrate assemblages in streams of different land use. Highlights: Land-use in the basin affects the invertebrate assemblages in Pampean streams. Pesticide and nutrients were higher at agriculture sites. Palaemonidae (Decapoda) and Caenidae (Ephemeroptera) were dominant in a reserve. Hyalellidae (Amphipoda) and Hirudinea were dominant at the streams surrounded by livestock fields. Oligochaeta and Hirudinea were dominant in the agricultural site.